2010
DOI: 10.1091/mbc.e09-12-1079
|View full text |Cite
|
Sign up to set email alerts
|

A Domesticated piggyBac Transposase Plays Key Roles in Heterochromatin Dynamics and DNA Cleavage during Programmed DNA Deletion in Tetrahymena thermophila

Abstract: Transposons comprise large fractions of eukaryotic genomes and provide genetic reservoirs for the evolution of new cellular functions. We identified TPB2, a homolog of the piggyBac transposase gene that is required for programmed DNA deletion in Tetrahymena. TPB2 was expressed exclusively during the time of DNA excision, and its encoded protein Tpb2p was localized in DNA elimination heterochromatin structures. Notably, silencing of TPB2 by RNAi disrupts the final assembly of these heterochromatin structures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
236
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(253 citation statements)
references
References 45 publications
14
236
0
3
Order By: Relevance
“…Previous studies have shown that many heterochromatin components are required for DNA elimination and for the production of viable sexual progeny (Coyne et al, 1999;Mochizuki et al 2002;Malone et al, 2005;Liu et al, 2007;Cheng et al, 2010). DNA elimination in the exconjugants (progeny) of JUB6 MIC-KO was analyzed by using DNA fluorescent in situ hybridization (FISH) with probes complementary to the Tlr1 IESs, which show moderate levels of repetition (Wuitschick et al, 2002).…”
Section: Jub6p Is Important For Dna Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that many heterochromatin components are required for DNA elimination and for the production of viable sexual progeny (Coyne et al, 1999;Mochizuki et al 2002;Malone et al, 2005;Liu et al, 2007;Cheng et al, 2010). DNA elimination in the exconjugants (progeny) of JUB6 MIC-KO was analyzed by using DNA fluorescent in situ hybridization (FISH) with probes complementary to the Tlr1 IESs, which show moderate levels of repetition (Wuitschick et al, 2002).…”
Section: Jub6p Is Important For Dna Eliminationmentioning
confidence: 99%
“…The first group consists of proteins required for the formation of heterochromatin at IESs, including the RNAi machinery components Dcl1p, Twi1p, Giw1p and Ema1p, the histone methyltransferase Ezl1p and the HP1-like protein Pdd1p (Aronica et al, 2008;Coyne et al, 1999;Liu et al, 2004Liu et al, , 2007Malone et al, 2005;Mochizuki and Gorovsky, 2005;Noto et al, 2010). The second group includes proteins that are dispensable for heterochromatin formation but are required for its assembly into heterochromatin bodies: Jub1p, Lia1p, Lia4p, Lia5p, Pdd2p, Tku80p and Tpb2p Rexer and Chalker, 2007;Horrell and Chalker, 2014;Shieh and Chalker, 2013;Liu et al, 2007;Cheng et al, 2010;Lin et al, 2012;Vogt and Mochizuki, 2013;Kataoka and Mochizuki, 2015). Although some of the mechanisms responsible for the former RNAi-directed heterochromatin formation process have been elucidated at the biochemical level, the latter heterochromatin body formation process remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…These small RNAs are bound by the piwi-related Tetrahymena argonaute proteins Twi1p and Twi11p (Mochizuki et al, 2002;Couvillion et al, 2009;Noto et al, 2015) and are thought to guide heterochromatin targeting through homology recognition, though the targeting mechanism is still unknown. The targeted regions are modified with silencing marks, including specific histone modifications and chromodomain proteins (Taverna et al, 2002;Liu et al, 2004Liu et al, , 2007Yao and Chao, 2005), leading to their excision using a domesticated piggyBac transposase, Tpb2p (Cheng et al, 2010;Chalker and Yao, 2011). Remarkably, injections of dsRNAs into developing cells causes efficient deletion of the corresponding macronuclear DNA from the progeny (Yao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The clones 6-1, 9-2, 9-6, 17-1 of TTHERM_00301940 KO cells were selected for further study. TTHERM_00301940 is exclusively expressed during conjugation and many conjugation-specific genes are required for DNA elimination (Mochizuki et al 2002;Taverna et al 2002;Liu et al 2007;Cheng et al 2010;Shieh and Chalker 2013;Woehrer et al 2015); we sought to determine whether TTHERM_00301940 is also involved in DNA elimination. TTHERM_00301940 KO strains (6-1 3 9-6 [= cross 1 in Table 1] or 9-2 3 17-1 [= cross 2 in Table 1]) were mated, and the DNA elimination in their exconjugants (progeny) was analyzed by DNA FISH using probes complementary to the Tlr1 element.…”
mentioning
confidence: 99%
“…In contrast to the gene KO strategies, RNAi KD can be done in a shorter period of time and is thus suitable for high-throughput genetic screening. However, RNAi KD often only incompletely shuts down expression of a target gene (Howard-Till and Yao 2006;Cheng et al 2010;Chung and Yao 2012;Lukaszewicz et al 2013) and may thus result in the misinterpretation of the gene function. During the development of the new MAC of Tetrahymena, .8000 DNA segments called internal eliminated sequences (IESs) were reproducibly eliminated.…”
mentioning
confidence: 99%